2014
DOI: 10.3945/jn.113.186775
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Overnutrition Programs Changes in the Expression of Skeletal Muscle Genes That Are Associated with Insulin Resistance and Defects of Oxidative Phosphorylation in Adult Male Rat Offspring

Abstract: Children of obese mothers have increased risk of metabolic syndrome as adults. Here we report the effects of a high-fat diet in the absence of maternal obesity at conception on skeletal muscle metabolic and transcriptional profiles of adult male offspring. Female Sprague Dawley rats were fed a diet rich in saturated fat and sucrose [high-fat diet (HFD): 23.5% total fat, 9.83% saturated fat, 20% sucrose wt:wt] or a normal control diet [(CD) 7% total fat, 0.5% saturated fat, 10% sucrose wt:wt] for the 3 wk prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
78
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 47 publications
2
78
1
Order By: Relevance
“…Consistently, decreased activities of antioxidative enzymes (SOD, GPx and CAT) and increased MDA levels were also observed in skeletal muscle of HE fetuses, suggesting the failure of ROS defense system and more, which is probably one of the major determinants of mitochondrial function alterations (Bonnard et al, 2008). In addition, several studies have shown mitochondrial dysfunction can affect whole-body metabolism and play an important in the pathophysiology of insulin resistance in offspring of high-fat diet-fed dams (Bonnard et al, 2008;Latouche et al, 2014). In accordance with previous work (Raipuria et al, 2015), in the current study the fetuses from HE sows had a potential risk for metabolic disorder with higher insulin and triglyceride concentrations in umbilical vein serum compared with fetuses from NE sows.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Consistently, decreased activities of antioxidative enzymes (SOD, GPx and CAT) and increased MDA levels were also observed in skeletal muscle of HE fetuses, suggesting the failure of ROS defense system and more, which is probably one of the major determinants of mitochondrial function alterations (Bonnard et al, 2008). In addition, several studies have shown mitochondrial dysfunction can affect whole-body metabolism and play an important in the pathophysiology of insulin resistance in offspring of high-fat diet-fed dams (Bonnard et al, 2008;Latouche et al, 2014). In accordance with previous work (Raipuria et al, 2015), in the current study the fetuses from HE sows had a potential risk for metabolic disorder with higher insulin and triglyceride concentrations in umbilical vein serum compared with fetuses from NE sows.…”
Section: Discussionmentioning
confidence: 80%
“…Here, we use pig as model based on the higher similarities of pig to human in physiology and genome (Merrifield et al, 2011). Cumulative evidence strongly indicates that reduction in mitochondrial function and oxidative metabolism in skeletal muscle during critical period of fetus growth and development was associated with the greater incidence of T2D and insulin resistance in later life (Shelley et al, 2009;Latouche et al, 2014). In the present study, the intriguing findings were that HE fetuses exhibited High-energy diet affects mitochondrial biogenesis decreased skeletal muscle mitochondrial biogenesis in response to maternal HE intake on day 90 of gestation compared with NE fetuses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin resistance or deficiency alters the regulation of these processes and causes elevated fasting and postprandial levels of glucose and lipids. Maternal obesity (MO) is increasing worldwide and is an important risk factor contributing to type 2 diabetes in offspring (Wang & Lobstein 2006, Samuelsson et al 2008, Gonzalez et al 2013, Latouche et al 2014. Type 2 diabetes is polygenic and may involve polymorphisms in multiple genes encoding proteins involved in 231:1 insulin signaling, insulin secretion and intermediary metabolism (Stern 2000, Kahn et al 2006.…”
Section: Introductionmentioning
confidence: 99%